DETERMINATION OF LOCAL BRITTLE ZONES AT THE CRACK FRONT IN THE HAZ OF WELDED JOINT - Praunseis, Zdravko; Mlakar, Marko; Novak, Sonja (Journal of Energy Technology, 2024)
Welded joints are the weakest link in the construction of steel structures. The brittlest part of a multi-pass welded joint is the heat-affected zone, where brittle fractures of the structure often appear. In this article, examination of the whole heat-affected zone of high strength multipass X welded joints was performed. All microstructures and the local brittle zones’ sizes at the crack tip front were precisely determined